Isolasi dan Karakterisasi Morfologi Bakteri Dekomposer Asal Rhizosfer Tanaman Bambu dari Kabupaten Sidrap, Sulawesi Selatan - Mu'minah,; Darmawan,; Darwisah, Baso; Isnaini, Junyah Leli; Mutalib, Abdul; Ashan, Muh. Dzulkifly; Ismail, Sarief; Yuniarti, Erny (Journal Galung Tropika, 2025)
The utilization of microorganisms that can accelerate the composting process is the utilization of decomposing bacteria from decomposer products that are useful for accelerating the decomposition process of organic materials. This study aims to obtain bacterial isolates that can function as agricultural waste decomposers from bamboo rhizosphere from Sidrap Regency. This study consists of 4 stages, namely (i) Sampling in the bamboo plant rhizosphere, (ii) Isolation of rhizosphere soil samples, (iii) Identification of microorganism morphology, (iv), and the last stage is testing the ability to degrade cellulose (cellulolytic). The study results showed that in Sidrap Regency, there were 4 sampling points, namely at S 030 57 '25.4 "and E 1190 40'44. 9" and S 03056'09.7 "and E 1190 41'24.9". There, 52 isolates were successfully isolated from the four places. Isolates SDR1A101B and SDR1A107B have the best ability to degrade and decompose cellulose.